SISTEM SAPAAN DALAM BAHASA DAYAK TAMAMBALOH DI DESA BANUA UJUNG KABUPATEN KAPUAS HULU - Paitingan, Oktaviana; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is triggered by the importance of greetings in accordance with the greeting system in a language, because the greeting system serves to respect and the media to express politeness to the speech partners. Thus, the follow-up to documenting the greeting system in the Dayak Tamambaloh language is considered necessary, because it can be an example and reference for the community. This research describe the use of greetings in the Dayak Tamambaloh language in Kapuas Hulu Regency, which is based on the type when the greetings are used, the lingual form of greetings, the selection factors and the function of the greeting, and the greeting system. Using descriptive method. The data source was a direct speech by the Dayak Tamambaloh people in Banua Ujung village, Kapuas Hulu Regency. The data was collected using note-taking techniques and recording techniques. The tools used are data cards, questionnaires, recording devices, and lists of greeting words. Data analysis in this research includes, transcription, classification, data analysis, and conclusion. Data analysis conclude that the speech was divided into 1) the type of greeting used; self-name, pronouns, kinship, and non-friendship. 2) greeting lingual forms; words, and phrases. 3) voting factors and greeting functions in the Dayak Tamambaloh language in the family, religious and community domains are influenced by age, gender, social status, familiarity, differences in kinship and function as a tool to call, respect, communication tools and tools for thinking . 4) greeting system; kinship relationship due to blood relations, and kinship relationships due to marital relations.Â Keywords: Greeting System, Tamambaloh Dayak Language, Lingual Form, ElectionÂ Factor